Targeting the Glucocorticoid Receptors During Alcohol Withdrawal to Reduce Protracted Neurocognitive Disorders - Béracochéa, Daniel; Mons, Nicole; David, Vincent (Frontiers in Psychiatry, 2019)
Persistent regional glucocorticoids (GCs) dysregulation in alcohol-withdrawn subjects emerges as a key factor responsible for protracted molecular and neural alterations associated with long-term cognitive dysfunction. The demonstration that regional brain concentrations of corticosterone can change in alcohol withdrawn subjects independently from plasma concentrations may have important implications for the treatment of alcohol withdrawal-induced persistent pathology. Thus, from a pharmacological point of view, a main issue remains to determine the relative efficacy of compounds targeting the GCs receptors to attenuate or suppress the long-lasting persistence of brain regional GCs dysfunctions in abstinent alcoholics, as well as persistent changes of neural plasticity. Data from animal research show that acting directly on GCs receptors during the withdrawal period, via selective antagonists, can significantly counteract the development and persistence of cognitive and neural plasticity disorders during protracted abstinence. A critical remaining issue is to better assess the relative long-term efficacy of GC antagonists and other compounds targeting the corticotropic axis activity such as GABAA and GABAB agonists. Indeed, benzodiazepines (acting indirectly on GABAA receptors) and baclofen (agonist of the GABAB receptor) are the compounds the most widely used to reduce alcohol dependence. Clinical and preclinical data suggest that baclofen exerts an effective and more powerful counteracting action on such persistent cognitive and endocrine dysfunctions as compared to diazepam, even though its potential negative effects on memory processes particularly at high doses should be better taken into account.